Narrative strategies for a pluralistic understanding of the Chinese revolution. Issue 4 (6th June 2016) - Shu, Yunzhong
Abstract : Univocality has remained a central characteristic of modern Chinese literature. As a narrative strategy, it has been employed not only as a weapon against tradition, but also as a propagandist tool after the Communist takeover in 1949. What would happen to this natural ally of the Communist regime when the regime itself began to lose faith in its ideology and become less authoritarian in the reform era? This article discusses the Chinese writer Zhou Meisen's subversion of univocality in his novel Heavy Yoke ( Zhong e, 1988). Utilising Bakhtin's theories of polyphony, field of vision and his philosophy of the act, it analyses Zhou's representation of the Chinese revolution from perspectives long suppressed or ignored by the Communist regime. While focusing on Zhou's local approaches to the complexities of the Chinese revolution, it examines, in particular, Zhou's rejection of the omniscient viewpoint as inadequate to capture the specificities and potentialities of history. Ultimately, it makes the point that Zhou's emphasis on perspectival inclusiveness is aimed at challenging Marxism's scientific understanding of history.